Perkembangan Upaya Pemberantasan Kartel Internasional Menggunakan Leniency Program - Alifudin Al Azlansyah; Talitha Maritza Fauziyyah; Muhammad Shidqi Abiyu Khuzaeni; Sarpini Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Leniency Program is a partial or total reduction in fines or penalties granted by competition authorities to companies involved in cartel practices. This program is implemented in various countries, including the European Union, the United States and Australia, to uncover cartel practices by providing incentives in the form of reduced or eliminated sanctions for businesses that report their involvement and provide evidence. The negative impact that cartel practices have on competition and consumers, as well as the legal framework in various countries, including Indonesia. This research uses a qualitative desk study approach, analyzing secondary data from relevant literature. The findings show that leniency programs are an effective tool to uncover hidden cartel activity, although challenges remain, such as ensuring legal protection for whistleblowers and tailoring strategies to the local legal context.